Development, content validity, and cross‐cultural adaptation of a patient‐reported outcome measure for real‐time symptom assessment in irritable bowel syndrome. Issue 3 (6th November 2017) - Vork, L.; Keszthelyi, D.; Mujagic, Z.; Kruimel, J. W.; Leue, C.; Pontén, I.; Törnblom, H.; Simrén, M.; Albu‐Soda, A.; Aziz, Q.; Corsetti, M.; Holvoet, L.; et al.
Abstract: Background: End‐of‐day questionnaires, which are considered the gold standard for assessing abdominal pain and other gastrointestinal (GI) symptoms in irritable bowel syndrome (IBS), are influenced by recall and ecological bias. The experience sampling method (ESM) is characterized by random and repeated assessments in the natural state and environment of a subject, and herewith overcomes these limitations. This report describes the development of a patient‐reported outcome measure (PROM) based on the ESM principle, taking into account content validity and cross‐cultural adaptation. Methods: Focus group interviews with IBS patients and expert meetings with international experts in the fields of neurogastroenterology & motility and pain were performed in order to select the items for the PROM. Forward‐and‐back translation and cognitive interviews were performed to adapt the instrument for the use in different countries and to assure on patients' understanding with the final items. Key results: Focus group interviews revealed 42 items, categorized into five domains: physical status, defecation, mood and psychological factors, context and environment, and nutrition and drug use. Experts reduced the number of items to 32 and cognitive interviewing after translation resulted in a few slight adjustments regarding linguistic issues, but not regarding content of the items. Conclusions and Inferences: An ESM‐based PROM, suitable for momentary assessment of IBS symptom patterns was developed, taking into account content validity and cross‐cultural adaptation. This PROM will be implemented in a specifically designed smartphone application and further validation in a multicenter setting will follow. Abstract : Retrospective patient reports of IBS symptoms are influenced by recall and ecological bias. A digital patient‐reported outcome measure (PROM) for momentary symptom assessment in IBS, based on the experience sampling methodology (ESM), was developed, taking into account content validity and cross‐cultural adaptation. The developed ESM‐PROM assesses real‐time symptoms and influencing factors in daily life, and therefore has the potential to provide insight into the fluctuating IBS symptom pattern during the day and to identify individual symptom triggers.